Molecular mechanisms of premature ageing in a worm model of human Werner syndrome - Lees, H; Hayley Lees (2014)
Investigating the biological basis of ageing is both fascinating and medically relevant, as we strive to understand both how organisms age, and how our knowledge might be put to good use in an increasingly long-lived human population. Despite the complexity of ageing biology, it is very striking that longevity, in a wide variety of organisms, can be modified by manipulating single genes. In this thesis, I investigate phenotypes associated with mutations in C. elegans homologues of human WRN, the gene mutated in the progeroid Werner syndrome (WS). Mutant phenotypes in the worm recapitulate aspects of the pathophysiology observed in WS patients, including premature ageing, genomic instability, and sensitivity to DNA damaging agents. wrn-1 overexpression, on the other hand, appears to enhance longevity, suggesting that wrn-1 acts as a bona fide anti-gerontogene. The combination of wrn-1 mutations with mutation in the worm p53 homologue, cep-1, unexpectedly triggers a novel and very striking enhanced lifespan and healthspan phenotype, termed synthetic super-viability (SSV). The SSV phenotype is modulated by various environmental inputs such as temperature stress. The data presented here can be incorporated into a model in which stress sensing (involving p53) is the crucial determinant of longevity outcomes. Several theories of ageing incorporate the idea that 'that which does not kill us, makes us stronger' - encapsulated in a biological sense in the idea of hormesis, a physiological shift in response to stress. Here, this hypothesis is expanded to include the notion that intrinsic responses to stress may themselves act to limit lifespan - too much of a good thing can be bad.